If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 3 + 7x + 16x + -1 = x Reorder the terms: 3 + -1 + 4x + 7x + 16x = x Combine like terms: 3 + -1 = 2 2 + 4x + 7x + 16x = x Combine like terms: 4x + 7x = 11x 2 + 11x + 16x = x Combine like terms: 11x + 16x = 27x 2 + 27x = x Solving 2 + 27x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 2 + 27x + -1x = x + -1x Combine like terms: 27x + -1x = 26x 2 + 26x = x + -1x Combine like terms: x + -1x = 0 2 + 26x = 0 Add '-2' to each side of the equation. 2 + -2 + 26x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 26x = 0 + -2 26x = 0 + -2 Combine like terms: 0 + -2 = -2 26x = -2 Divide each side by '26'. x = -0.07692307692 Simplifying x = -0.07692307692
| -4(p-1)=-8 | | [5(c+1)]=(3c-14) | | 4/5•x=16/25 | | (X-2)(x-7)=(x+7)(x+8) | | 3+-3=-30 | | 4/5*x= | | 61=-3+8X | | -(7m+7)=-21 | | -9X+0=45 | | 10=u/12 | | 5b+30=8b | | (-6v^2+8v+9)-(9v^2+12v-4)= | | X(4x-2)=(4x+1)(x-2) | | -9X+7=-47 | | (4x-1)h-(4x-1)= | | 21.3x+1.6=47.6-1.7x | | (2r-3)-(-6r+7)= | | 6(x-7)-4(x+3)=-1 | | xsquared+4x+1=0 | | (x^3y^2)^5*(xy^5)^-2/x^3y^5 | | m/n=y/x | | 9a-2=16+3a | | 3a+-7a+12=32 | | gf=k | | f(x)=8x+18 | | (10m+14)=(3m+11) | | y=xa | | 3a-7a+1=32 | | -7x=49, | | (4v^2+12p^2+9)+(6v^2-6p^2-6)= | | -4x/1=5/6-5x/6 | | -9u-42=-6(u+6) |